Karakteristik Molekuler Virus Avian Orthoavulavirus 1 Genotipe VII yang Diisolasi dari Tabanan Bali (MOLECULAR CHARACTERISTIC OF AVIAN ORTHOAVULAVIRUS 1 GENOTYPE VII ISOLATED FROM TABANAN BALI) - Adi, Anak Agung Ayu Mirah; Astawa, I Nyoman Mantik; Wandia, I Nengah; Putra, I Gusti Agung Arta; Winaya, Ida Bagus Oka; Krisnandika, Anak Agung Keswari; Wijaya, Anak Agung Oka (Jurnal Veteriner; Vol 20 No 4 (2019), 2020)
Newcastle disease (ND) is a very harmful avian disease, endemic in Indonesia and various parts of the world. The causative agent is ND virus or Avian orthoavulavirus 1 (AOAV-1). This virus is an RNA virus with wide genetic variation. Based on the genome length, it can be classified into AOAV-1 Class I and II. Class I are generally avirulent whereas Class II are consist of both virulent and avirulent viruses, currently there are 18 genotypes of the class II. To find out the molecular characteristics of AOAV-1 currently circulating in the field, isolation and identification of viruses from laying hens that was suspected ND from Tabanan Bali in 2017, was performed. The isolated viruses hereafter named as Tabanan1/ARP / 2017. A one-step RT-PCR reaction was carried out to amplify NP, F and HN gene fragments from the virus using three specific pairs of AOAV-1 primers. The obtained nucleotide sequences are then used in phylogenetic analysis. For phylogenetic analysis several strains of AOAV-1 from class II representing genotype I-VII as well as one strain from Class I were accessed from GenBank. From the analysis of the F gene nucleotide sequences, it was found that Tabanan 1 / ARP / 2017 is a genotype VII virus with an amino acid sequence at the F protein cleavage site is 112 R-R-Q-K-R-F117, a typical virulent strain. Phylogenetic analysis using nucleotide sequences NP and HN genes also positioned this isolate in genotype VII. At the nucleotide level, genetic distance with virulent isolates that was isolated in 2007 and 2010 were 8.26% and 1.08% while at the amino acid level were 5.26% and 0.64%. There were found mutations in amino acids at positions 107 and 108 of  F protein.